Evaluating the capability of a critical state constitutive model to predict the collapse potential of loose sand. (August 2015) - Azizi, A; Bella, G; Farshchi, I
Abstract: Many catastrophic flow failures in granular soil slopes are believed to be caused by a rise in pore water pressure associated with substantial loss of soil shear strength. This failure mechanism is known as prefailure instability or static liquefaction. Constant shear (CS) and consolidated undrained (CU) triaxial tests can reproduce stress paths, in which such instability may occur before reaching the failure. In the present study, a previously proposed critical state constitutive model was first used to simulate the behavior of loose saturated sand in CU tests. It was then employed to predict the instability of loose sand subjected to the CS loading. Under such loading, loose dry sand initially experience small volume increase, and then start to contract substantially. In saturated sand, such contractions can lead to the generation of pore water pressure and sudden decrease of shear strength. The capability of the model to predict the onset of the volume contraction and collapse potential of loose dry sand was examined by comparing the model predictions with experimental results of CS tests. The comparison showed that the effect of initial void ratio, consolidation and deviatoric stresses on behavior of loose dry sand can be well predicted by the model.